2007
DOI: 10.1017/s1431927607070341
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Uranium Particles Produced by Hydrolysis of UF6Using SEM and SIMS

Abstract: Environmental sampling (ES) is a powerful technique used by safeguards inspectors of the International Atomic Energy Agency and the European Safeguards Office for the detection of undeclared nuclear activities. Since its implementation in the 1990s, ES has proven to be very sensitive and effective. Considering the consequences, the measurements should be carried out under a quality management programme. At the Institute for Reference Materials and Measurements, a new production method is under development for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 14 publications
3
43
0
Order By: Relevance
“…4 In that work, researchers found only UO 2 F 2 product for UF 6 these two values and no reaction mechanisms were proposed. Additionally, several groups have studied the particle morphology [5][6][7][8][9][10] and reactor design for the production of particles from aerosols of UF 6 . 11…”
Section: Uf 6 + H 2 O → Uof 4 + 2hfmentioning
confidence: 99%
“…4 In that work, researchers found only UO 2 F 2 product for UF 6 these two values and no reaction mechanisms were proposed. Additionally, several groups have studied the particle morphology [5][6][7][8][9][10] and reactor design for the production of particles from aerosols of UF 6 . 11…”
Section: Uf 6 + H 2 O → Uof 4 + 2hfmentioning
confidence: 99%
“…A glass or metal sample holder with UF 6 was pressurized with heat, allowing the UF 6 to be released as a liquid. Analyses of the products formed indicated that aggregate particle morphologies and size distributions of the settled products were dependent upon relative humidity, temperature of the UF 6 , and time (hours) [14,15]. In this latter study, UF 6 was contained in glass that was mechanically ruptured, allowing the compound to hydrolyze with air in a surrounding enclosure.…”
Section: *Manuscriptmentioning
confidence: 87%
“…SEM-EDS spectra indicated that the major elemental constituents were uranium, oxygen and fluorine (Supporting Information Figure S In contrast, Pickrell observed formation of ~ 10 μm agglomerates made of discrete spheroids on the order of 0.1 μm in diameter following release of liquid UF 6 to excess water, and suggested that agglomeration of particles over time was likely due to charging [11,12]. Kips reported an increase in the average particle diameter with increased relative humidity [15]. Because the morphologic shapes of the materials deposited onto a carbon conductive surface were consistent with these prior experimental measurements and analyses, we chose not to store these samples under controlled conditions.…”
Section: Hydrolysis Products Deposited Onto a Carbon Conductive Tapementioning
confidence: 99%
“…The spherical shape and size strongly indicates UO 2 F 2 . Several studies have shown that formation of UO 2 F 2 from UF 6 in a humid environment results in spherical shapes of about ≅0.2-2.0 μm diameter [33][34][35]. The presence of nitrogen is slightly surprising, but could be explained by attachment of nitrogen-rich materials present in the atmosphere.…”
Section: All Workhops -Aerosol Morphologymentioning
confidence: 99%